Dreams, Deception and Delusion: The Derailing of Ottawa’s Light Rail Transit Plans - Hilton, Robert; Stoney, Christopher (Revue Gouvernance / Governance Review, 2007)
In this article, the authors examine the failed City of Ottawa’s Light Rail Transit (LRT) project as a case study. While the LRT was trumpeted by local politicians and bureaucrats as a symbol of the city’s coming of age, the project was fraught with problems. The article explores these problems and points out that the way in which the project was managed is a cautionary tale in how not to promote large-scale public infrastructure projects.The authors point to the dangers that occur when those who make decisions about the expenditure of public funds become promoters of a project. There are serious risks when political commitments are made early on in a project’s development and appraisal stage. Rather than remaining focused on achieving levels of service within costs that are acceptable to those who pay for these services, decision makers can fall into the trap of ‘boosterism’that puts ego and status ahead of public interest.